Advancements in Regenerative Strategies Through the Continuum of Burn Care - Stone II, Randolph; Natesan, Shanmugasundaram; Kowalczewski, Christine J.; Mangum, Lauren H.; Clay, Nicholas E.; Clohessy, Ryan M.; Carlsson, Anders H.; Tassin, David H.; Chan, Rodney K.; Rizzo, Julie A.; Christy, Robert J. (Frontiers in Pharmacology, 2018)
Burns are caused by several mechanisms including flame, scald, chemical, electrical, and ionizing and nonionizing radiation. Approximately half a million burn cases are registered annually, of which forty thousand patients are hospitalized and receive definitive treatment. Burn care is very resource intensive as the treatment regimens and length of hospitalization are substantial. Burn wounds are classified based on depth as superficial (first degree), partial-thickness (second degree), or full-thickness (third degree), which determines the treatment necessary for successful healing. The goal of burn wound care is to fully restore the barrier function of the tissue as quickly as possible while minimizing infection, scarring, and contracture. The aim of this review is to highlight how tissue engineering and regenerative medicine strategies are being used to address the unique challenges of burn wound healing and define the current gaps in care for both partial- and full-thickness burn injuries. This review will present the current standard of care and provide information on various treatment options that have been tested pre-clinically or are currently in clinical trials. Due to the complexity of burn wound healing compared to other skin injuries, burn specific treatment regimens must be developed. Recently, tissue engineering and regenerative medicine strategies have been developed to improve skin regeneration that can restore normal skin physiology and limit adverse outcomes, such as infection, delayed re-epithelialization, and scarring. Our emphasis will be centered on how current clinical and pre-clinical research of pharmacological agents, biomaterials, and cellular-based therapies can be applied throughout the continuum of burn care by targeting the stages of wound healing: hemostasis, inflammation, cell proliferation, and matrix remodeling.